PENGARUH BUDAYA INGGRIS RAYA DALAM DESAIN MONSTER DAN WORLD BUILDING GAME “POKEMON SWORD” DAN “POKEMON SHIELD” - Nabila Husna Al'Arifah; Dianing Ratri; Irfansyah Irfansyah (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2022)
Pokemon Sword and Pokemon Shield is a pair of Role Playing Game (RPG) that were released for Nintendo Switch Console. Pokemon itself is known as the monster collecting game, as their slogan,